Environmental sustainability practices and strategies in the rural tourism and hospitality sector: a systematic literature review and suggestions for future research. Issue 1 (1st January 2023) - Madanaguli, Arun; Dhir, Amandeep; Joseph, Rojers P.; Albishri, Norah Ali; Srivastava, Shalini
ABSTRACT: Environmental sustainability in the rural tourism and hospitality (hereafter abbreviated RT) sector has received increased attention in the last decade. Although several reviews have examined sustainable tourism, a dedicated review of environmental sustainability initiatives in the RT sector is absent. To address this gap, we present a systematic literature review of 100 research articles addressing RT and environmental sustainability from 39 journals. The review indicates that this area is growing and primed for further research. We present three main contributions. First, we identify different stakeholders of RT environmental sustainability. Second, we summarize the driving and barrier roles of each stakeholder in environmentally sustainable RT. Third, we present the benefits of environmentally sustainable RT. We observe the pivotal roles played by entrepreneurs, community, tourists, and policymakers in the development of environmentally sustainable RT but note that stakeholders like corporations, non-governmental organizations, and media have received little or no attention. Based on the gaps we identified, we outline five suggestions for future research in the area and present for each a variety of possible research questions. We then summarize our findings into a RT environmental sustainability framework and discuss the academic, practical, and policy implications of the study.